The elephant whisperer [compact disc, unabridged] : my life with the herd in the African wild - Anthony, Lawrence; Spence, Graham (Tantor Media, Inc., 2012)
African conservationist Lawrence Anthony accepted a herd of rogue wild elephants on his game reserve in Zululand because he was the herd's last chance for survival. In the years that followed he became a part of their family. And as he battled to create a bond with the elephants, he came to realize that they had a great deal to teach him about life.